Green Marketing, Greenwashing, and Premium Pricing Effects on Agrochemical Sales Performance: Pengaruh Green Marketing, Greenwashing, dan Penetapan Harga Premium terhadap Kinerja Penjualan Agrokimia - Andreas Marcellius Stevenson; Teofilus Teofilus; Lexi Pranata Budidharmanto (Academia Open, 2026)
General Background: The agrochemical industry faces growing public scrutiny as sustainability concerns and environmental risks of synthetic chemicals intensify, prompting firms to integrate sustainability-oriented strategies into their business models. Specific Background: In Indonesia, agrochemical companies increasingly rely on green marketing communication, sustainability claims, and premium pricing to position green chemical products amid regulatory pressure and rising environmental awareness. Knowledge Gap: Empirical evidence remains limited regarding how green marketing, greenwashing practices, and premium pricing are simultaneously associated with sales performance in the agrochemical sector, particularly from the perspective of marketing practitioners. Aims: This study examines the relationships between green marketing strategies, greenwashing practices, and premium pricing with the sales performance of green chemical products, while assessing the moderating role of premium pricing. Results: Quantitative analysis using regression and moderated regression analysis indicates that green marketing, greenwashing, and premium pricing are each positively and significantly associated with sales performance, whereas premium pricing does not significantly moderate the relationships between green marketing or greenwashing and sales performance. Novelty: The study demonstrates that, within the Indonesian agrochemical context, greenwashing practices can be associated with short-term sales performance alongside green marketing and premium pricing. Implications: The findings suggest that agrochemical firms should prioritize credible and transparent sustainability communication and apply value-based pricing, as sales performance is driven by direct strategic signals rather than interaction effects among sustainability marketing and pricing strategies. Highlights: Sustainability-oriented communication shows a positive association with product sales outcomes. Short-term market gains are observed alongside unverified environmental claims. Price positioning serves as a direct market signal rather than an interaction mechanism. Keywords: Green Marketing, Greenwashing, Premium Pricing, Sales Performance, Agrochemical Industry.